Failure analysis of girth weld cracking of mechanically lined pipe used in gasfield gathering system. (October 2016) - Fu, A.Q.; Kuang, X.R.; Han, Y.; Lu, C.H.; Bai, Z.Q.; Yin, C.X.; Miao, J.; Feng, Y.R.; Wei, Y.G.; Tang, Q.; Yang, Y.
Abstract: Girth weld cracking of mechanically lined pipe was occurred after 75 days operation in a gasfield gathering system in China. Failure causes were analyzed based on operation histories, field documents, and laboratory tests. Results showed that the girth weld failure was mainly due to two aspects, girth weld martensite microstructure and external stress. The crack was initiated from sealing pass zone and filling pass zone, which is a hard and brittle martensite structure with hardness of HV 350–450. The failed pipe area had undergone the heavy rain for 2 days, pulling stress, bending stress, and shear stress generated by soil movement resulted in high stress concentration at girth weld. The girth weld cracking failure was initiated from outer carbon steel, and propagated along the weld-fusion line in intergranular mode, which is a typical stress corrosion cracking failure. Highlights: The mechanically lined pipe crack initiated from outer carbon steel, and propagated in intergranular mode along the weld-fusion line Martensite structure formed at sealing pass zone and filling pass zone is the root cause of mechanically lined pipe cracking failure Pulling stress, bending stress, and shear stress caused by soil movement resulted in high stress concentration at girth weld